Social Innovation - Lee, Peter (Washington University Law Review, 2014)
This Article provides the first legal examination of the immensely valuable but underappreciated phenomenon of social innovation. Innovations such as cognitive behavioral therapy, microfinance, and strategies to reduce hospital-based infections greatly enhance social welfare yet operate completely outside of the patent system, the primary legal mechanism for promoting innovation. This Article draws on empirical studies to elucidate this significant kind of innovation and explore its divergence from the classic model of technological innovation championed by the patent system. In so doing, it illustrates how patent law exhibits a rather crabbed, particularistic conception of innovation. Among other characteristics, innovation in the patent context is individualistic, arises from a discrete origin and history, and prioritizes novelty. Much social innovation, however, arises from communities rather than individual inventors, evolves from multiple histories, and entails expanding that which already exists from one context to another. These  Professor of Law and Chancellor’s Fellow, UC Davis School of Law. I would like to thank Camilla Hrdy, Chris Griffin, Richard Gruner, Courtney Joslin, Lydia Loren, Manesh Patel, and Darien Shanske for their comments on earlier versions of this paper. This Article benefitted substantially from presentations at the Intellectual Property Scholars Conference at Cardozo Law School, the East Bay Faculty Workshop, the Works in Progress Intellectual Property colloquium at Santa Clara School of Law, IP in The Trees at Lewis & Clark Law School, PatCon 4 at the University of San Diego School of Law, the Value Pluralism and Intellectual Property Law conference organized by the University of Hong Kong Faculty of Law and the University of Pennsylvania Law School, and BYU Law School. I would like to thank Dean Kevin Johnson and Associate Dean Vik Amar for providing generous institutional support for this project. I would also like to thank Erin Choi and the UC Davis School of Law library staff for exceptional research assistance. Finally, I would like to thank the excellent editors of the Washington University Law Review. 2 WASHINGTON UNIVERSITY LAW REVIEW [VOL. 92:1 attributes, moreover, apply in large part to technological innovation as well, thus revealing how patent law relies upon and reinforces a rather distorted view of the innovative processes it seeks to promote. Moving from the descriptive to the prescriptive, this Article cautions against extending exclusive rights to social innovations and suggests several nonpatent mechanisms for accelerating this valuable activity. Finally, it examines the theoretical implications of social innovation for patent law, thus helping to contribute to a more holistic framework for innovation law and policy.
Keywords: Droit; Innovation; Valorisation

“Opening Innovation” Across Layers of Practices: Developing an Integrative View of the Emergence of Digital Health - Dionne, Karl-Emanuel; Carlile, Paul (Managing Inter-organizational Collaborations: Process Views, 2019)
Innovation challenges are increasingly complex, cutting across distributed actors from different disciplines, organizations, and fields. Solving such challenges requires creating the capacities of opening up for innovation to access and develop a greater amount and variety of knowledge and resources. Perspectives on open source, open innovation, and interorganizational collaboration have explored such capacities, but from different origins and scopes of analysis. Our practice-based integrative framework of “opening innovation” helps highlight these differences and connect their relative strengths. Through a critical literature review paired with an analysis of different empirical cases from Hacking Health, a non-profit organization helping drive digital health innovation, the authors reveal the user-centric, firm-centric, and field-centric approaches to opening innovation that progressively connect a greater variety of actors and resources. The authors show how specific new relational practices they produce address the new relational dynamics these connections bring to accumulate more resources for innovation to keep progressing.
Keywords: Collaboration interorganisationnelle; Healthcare; Innovation ouverte; Open source

Le droit d'auteur en 2021 : où en sommes-nous? - ROBIC (ROBIC, 2021)
Il nous fait plaisir de mettre à votre disposition l'enregistrement de la formation de Me Cara Parisien et Me Elodie Dion donnée le 6 avril 2022.

Guide sur le droit d'auteur - Bibliothèques UdeM (Bibliothèques - Université de Montréal)

Droit d'auteur - YouTube - Bibliothèques UdeM

Technology-transfer offices and academic open labs as different types of organizational intermediaries in science-society relationships - Mérindol, Valérie; Gallié, Emilie Pauline; Capdevila, Ignasi (Gestion 2000, 2018)
Cet article étudie les caractéristiques des structures de transfert technologique et des laboratoires d’innovation ouverte gérés par les universités et organismes de recherche. Il compare leurs rôles comme intermédiaires des relations science–entreprises en fonction des modes 2 et 3 de production des connaissances proposés par Etzkowitz & al (1997) et Carayannis & al (2009). Basée sur une comparaison de cas multiples en France, nous analysons leur rôle dans le développement des relations science-entreprise. Cet article identifie aussi les modes de coordination entre ces deux types d’intermédiaires. Dans certains cas, ils coordonnent leurs activités de manière ponctuelle alors que, dans d’autres cas, la complémentarité de leurs activités s’organise sur la durée.
Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 1 Publisher: Association de Recherches et Publications en Management
Keywords: Europe; France; Réservé UdeM; Rôle des universités; Technologie; Transfert; Valorisation